Information services for innovative organizations - Kazlauskas, Edward John; Weir, Anthony D. (Academic Press, 1994)
This well-written guide for the design and management of information services is tailored to suit the needs of students in information services management, both in schools of library and information science and in schools of business management. It is also intended for practitioners, librarians and other managers - who provide information to services in business, industry, and government, either from within an organization or as external consultants and contractors. In addition this book will assist those managers of computer and communications facilities. This book offers a sound basis for the design and management of information services to: provide decision makers with help for the management of change; make corporate decision makers aware of information as an asset and as a strategy for improved, innovative decisions; and make information service providers potential sources of innovation for any organization that processes information.
Keywords: Business information services.; Information organization.; elektronické knihy; electronic books